The Effect of Breathing Training in Choir Activities on Anxiety Levels in Adolescents: A Systematic Review - Ray Jeffrin; Lely Wahyuniar (Jurnal Edusci, 2025)
Background: Anxiety is a mental health problem that many adolescents experience and has an impact on academic, social, and long-term psychological well-being. Art-based nonpharmacological interventions, particularly choirs with breathing exercises, are reported to have the potential to reduce anxiety. However, systematic integration of scientific evidence remains limited. Objective: This systematic review aims to synthesize scientific evidence on the effect of breathing training during choir activities on anxiety levels in adolescents. Methods: The review was conducted following the PRISMA guidelines. Literature searches were conducted on Google Scholar, PubMed, and ScienceDirect for articles published in the last 10 years. Inclusion criteria include quantitative or mixed-methods studies of adolescents (ages 17–25) that examine breathing training in the context of choir or singing activities and measure anxiety as an outcome. Data is extracted and synthesized narratively. Results: A total of 8 articles met the inclusion criteria. The majority of studies reported a significant reduction in anxiety levels after a breathing training intervention in a choir. The mechanisms identified include activation of physiological relaxation responses, emotion regulation, increased focus, and social support through group activities. Conclusions: Breathing training in choir activities has the potential to be an effective and applicable nonpharmacological intervention to reduce anxiety in adolescents. However, the heterogeneity of the design and measurement instruments is a major limitation. Further research with a more robust experimental design is still needed.